Exploring and enhancing the volumetric behaviour in solar receivers through specular reflectivity and simplified design - Fathya Salih (16444569) (2023)
One of the remaining challenges of point focusing concentrating solar power systems is the realization of a true volumetric receiver, one whose entire volume is utilized for the absorption of irradiance. Commercial state-of-the-art receivers (e.g., HiTRec-II and SolAir-200) have not demonstrated the volumetric effect, because of low radiation penetration within the absorber. Then, literature state-of-the-art receivers were able to demonstrate a volumetric behaviour (toward achieving the volumetric effect) through axially varied macro-scale porosity (void fraction), but at the cost of design complexity and manufacturability. This study presents the conceptual design and computational assessment of an improved volumetric receiver by employing varied reflectivity on the irradiated surfaces, thereby enhancing radiation penetration. This approach maintains the simplicity, manufacturability, and commercial viability of structured receivers. Three reflectivity distributions were initially investigated using a 3D heat transfer mathematical model, verified with literature experimental data, which incorporated a source term ascertained through Monte-Carlo Ray Tracing (MCRT). The findings from these three design cases revealed that while diffuse reflectivity distributions could improve thermal efficiency, they were unable to enhance radiation penetration. Consequently, an improved volumetric solar receiver was realized by integrating specular reflectivity, leading to a more uniform source term distribution and achieving a thermal efficiency of 96%, as opposed to the 85% thermal efficiency of the commercial state-of-the-art HiTRec-II receiver. The discovery of the specular receiver as a true volumetric receiver facilitated an exploration of quantitative definitions of the volumetric effect. The exploration concluded that volumetric effect metrics would only target designs that maximizing thermal efficiency when the receiver is exhibits a truly volumetric nature, characterized by a uniform source term distribution. Other Information Published in: Energy Conversion and Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1016/j.enconman.2023.117306